Towards an improved understanding of angler tourism in northern Australia. (6th March 2013) - Greiner, R.; Franklin, D. C.; Gregg, D.
Abstract A human dimensions investigation into tourist anglers in a coastal recreational fishing hotspot in northern Australia is presented. Tourist anglers target one species, javelin grunter, Pomadasys kaakan (Cuvier), raising concerns about the sustainability of the fishery. Data from a survey of 427 tourist angling parties that fished in the coastal water off Karumba (Queensland) were analysed. Exploratory factor analysis was performed on angler target species and motivation for fishing to establish a typology of fishing intentions, with fishing for food found to be the principal factor. Anglers with high fishing for food factor scores were more consumptive, lower spending (per day) and more averse to any potential measures that might reduce legal possession (creel) limits or impose a cost of fishing. It was concluded that a combination of tourism and fisheries management interventions is required to safeguard Karumba's iconic javelin grunter fishery into the future. Diversification of tourist activity options can reduce the tourism industry's current reliance on high‐consumptive tourist anglers and increase the destination's appeal to non‐fishing tourists and low‐consumptive anglers. Modification of angler behaviour can be achieved through reduced possession limits for javelin grunter and possibly other target species, improved monitoring and law enforcement efforts, and targeted education and information.